Ensuring National Energy Security: The Role of PT Paiton Operation and Maintenance Indonesia in Sustainable Electricity Supply - Tristantri, Cepi Novia; Setowara, Subhan (The Republic of Indonesia Defense University, 2024)
The background of this research is the need for a stable and sustainable electricity supply to support economic growth and community welfare. This research aims to examine the important role of PT Paiton Operation and Maintenance Indonesia (PT POMI) in maintaining national electrical energy security in Indonesia, based on the components of energy security according to Cherp and Jewell: availability, accessibility, affordability, and environmental acceptability. The method used is descriptive qualitative with a case study at PT POMI, which is supported by primary and secondary data. Primary data comes from short in-depth interviews with PT POMI Production Department Staff, and secondary data comes from PT POMI archives, government policies, as well as journal articles and books related to the topic. Qualitative analysis techniques were used in this research because it is suitable for explaining what PT POMI does to ensure national electrical energy security. The findings reveal that PT POMI plays a vital role in ensuring energy availability through large-scale, stable electricity production; enhances accessibility via cooperation with PLN and infrastructure reliability; supports affordability through operational efficiency and CSR programs; and promotes environmental acceptability by adopting clean coal technology and implementing community-based conservation programs. The conclusion emphasizes that PT POMI significantly contributes to Indonesia’s national energy security by integrating sustainability, efficiency, and reliability in its operations, while aligning with the national energy transition agenda and environmental goals.